Perancangan Sistem Informasi Deteksi Gejala Stunting Anak Menggunakan Metode Certainty Factor Berbasis Website - Raihan Risky; Arpan; Muhammad Zen (CV. Hawari, 2026)
The grade data of students at SMK Swasta Rahmat Islamiyah Medan contains confidential information related to learning outcomes, performance evaluation, and student graduation. Currently, the risk of unauthorized access, data alteration, or deletion poses a threat to academic integrity, institutional reputation, and parents' trust. To overcome this issue, this study implements a symmetric cryptography method, specifically the Vernam Cipher algorithm, to secure student grade data. The Vernam Cipher encrypts data using a bitwise XOR (Exclusive OR) logical operation between plaintext and a secret key, ensuring that the stored or transmitted information remains unreadable to unauthorized parties. The results demonstrate that the application of Vernam Cipher effectively protects student grade data from manipulation and unauthorized leakage, maintaining data confidentiality and authenticity. Thus, this implementation supports a fair, secure, and reliable academic evaluation process at SMK Swasta Rahmat Islamiyah Medan.`